Analisis Faktor-Faktor Pemanfaatan Teknologi Informasi dan Dampaknya Terhadap Keahlian End User Computing (Euc) - Aswidani Aswidani; Yetty Yetty (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to determine the factors that influence IT utilization and its impact on end user computing (EUC). There are 2 categories of end users, namely ordinary end users (termed End users) and skilled end users (end user computing). End-users are people who interact with computer-based information systems only as consumers / users or people who need the results of software applications to carry out work, while End User Computing (EUC) is an end user who has expertise, so that he is able to solve computer problems appropriately. The importance of EUC in work activities is of concern to researchers. Some researchers use Information Technology (IT) utilization factors in measuring its impact on EUC. There are several IT utilization factors, including: Social Factors, Convenience Factors, Usability Factors and Long-term Consequences Factors. These 4 factors are used in this research. The research was conducted on second semester students of Management Study Program, Khairun University. Using multiple regression analysis. The result: there are 24% of students utilizing IT because of the convenience factor, although it is not significant. While social factors, usability factors and long-term consequences factors do not affect IT utilization. This explains that second semester students have not utilized Information Technology significantly, so there is no impact on EUC.